2012
DOI: 10.4314/ajtcam.v9i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants used for treatment of diabetes by the marakh sect of the Garo tribe living in Mymensingh district, Bangladesh

Abstract: Diabetes mellitus is an endocrinological disorder arising from insulin deficiency or due to ineffectiveness of the insulin produced by the body. This results in high blood glucose and with time, to neurological, cardiovascular, retinal and renal complications. It is a debilitating disease and affects the population of every country of the world. Around 200 million people of the world suffer from this disease and this figure is projected to rise to 300 million in the coming years. The disease cannot be cured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…It has several ethnopharmacological indications, such as antidiabetic (Rahmatullah et al, 2012), immunomodulatory , antidengue (Tang et al, 2012) and antioxidant activities (Aljohi et al, 2016), and has been shown to prevent hepatic fibrosis (Efird et al, 2014); in agriculture, it can be used to promote allelopathic activity (Singh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has several ethnopharmacological indications, such as antidiabetic (Rahmatullah et al, 2012), immunomodulatory , antidengue (Tang et al, 2012) and antioxidant activities (Aljohi et al, 2016), and has been shown to prevent hepatic fibrosis (Efird et al, 2014); in agriculture, it can be used to promote allelopathic activity (Singh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional medicinal systems in Bangladesh like Ayurveda, Unani or folk and tribal medicines have always placed emphasis on plants for treatment of diabetes [3,4]. Since Bangladesh is rich in fl oral species, we had been over the last few years systematically screening various plant extracts and polyherbal formulations for their antihyperglycemic activities as determined through oral glucose tolerance tests in mice [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Folk remedies for treatment of various diseases were prepared as infusions, powders, poultices, ointments, baths, creams, decoctions and teas. The interest in studying the biological effects of traditional medicinal plants or isolating their active components for treatment of illness has been increasing all over the world and comprehensive screening programs have been established 5,6 . The increased emergences of illness caused by pathogens have lead to the curiosity of many researchers and microbiological scientists in the investigation of antibacterial activities of medicinal plants which considered the main source of medicines to many African and Asian cultures since time immemorial.…”
Section: Introductionmentioning
confidence: 99%